The Effects of Intranasal Oxytocin Administration on Sensitive Caregiving in Mothers with Postnatal Depression - Mah, Beth L.; Van Ijzendoorn, Marinus H.; Out, Dorothee; Smith, Roger; Bakermans-Kranenburg, Marian J. (Child psychiatry and human development, 2017)
Postnatal depression (PND) is common and negatively affects the mother–infant relationship; oxytocin (OT) has been found to have positive effects on parenting, although psychiatric disorders may reduce these effects. Thus, we explored the role of OT in mothers diagnosed with PND. A within-subject, randomized controlled double-blind design was used to test the effects of nasal administration of OT or placebo on sensitive caregiving. The outcome measures were perceptual and caregiving responses to prerecorded cry sounds, as well as observed maternal sensitivity. We found that in the OT condition mothers with PND were more likely to rate an infant cry as more urgent and they were more likely to indicate they would chose a harsh caregiving strategy in response. There was no effect of OT on maternal sensitive interaction with their own baby. Further research is required prior to consideration of OT administration in depressed mothers of infants.